CYP2C19 polymorphism influences Helicobacter pylori eradication - Kuo, Chao-Hung; Lu, Chien-Yu; Shih, Hsiang-Yao; Liu, Chung-Jung; Wu, Meng-Chieh; Hu, Huang-Ming; Hsu, Wen-Hung; Yu, Fang-Jung; Wu, Deng-Chyang; Kuo, Fu-Chen (World journal of gastroenterology : WJG, 2014)
The known factors that have contributed to the decline of Helicobacter pylori(H.pylori)eradication rate include antibiotic resistance,poor compliance,high gastric acidity,high bacterial load,and cytochrome P450 2C19(CYP2C19)polymorphism.Proton pump inhibitor(PPI)is important in the eradication regimen.The principal enzyme implicated in the metabolism of PPIs is CYP2C19.The effects of PPI depend on metabolic enzyme,cytochrome P450 enzymes,and CYP2C19 with genetic differences in the activity of this enzyme(the homozygous EM,heterozygous EM(Het EM),and poor metabolizer).The frequency of the CYP2C19 polymorphism is highly varied among different ethnic populations.The CYP2C19genotype is a cardinal factor of H.pylori eradication in patients taking omeprazole-based or lansoprazolebased triple therapies.In contrast,the CYP2C19 polymorphism has no significant effect on the rabeprazolebased or esomeprazole-based triple therapies.The efficacy of levofloxacin-based rescue triple therapy might be also affected by the CYP2C19 polymorphism,but CYP2C19 genotypes did not show obvious impact on other levofloxacin-based rescue therapies.Choice of different PPIs and/or increasing doses of PPIs should be individualized based on the pharmacogenetics background of each patient and pharmacological profile of each drug.Other possible factors influencing gastric acid secretion(e.g.,IL-1β-511 polymorphism)would be also under consideration.